Refractory occipital neuralgia treatment with nerve decompression surgery: a case series - Austen, William G.; Remy, Katya; Packowski, Kathryn; Hazewinkel, Merel H. J.; Gfrerer, Lisa; Mathew, Paul G. (Frontiers in Neurology, 2023)
The management of refractory occipital neuralgia (ON) can be challenging.Selection criteria for occipital nerve decompression surgery are not well defined in terms of clinical features and best preoperative medical management.Methods: 15 patients diagnosed with ON by a board certified, fellowship trained headache specialist and referred to a plastic surgeon for nerve decompression surgery were prospectively enrolled. All subjects received trials of occipital nerve blocks (NB), at least 3 preventive medications, and onabotulinum toxin (BTX) prior to surgery before referral to a plastic surgeon. Treatment outcomes included headache frequency (headache days/month), intensity (0-10), duration (hours), and response to medication/injectable therapies at 12 months postoperatively.Results: Preoperatively, median headache days/month was 30 (20-30), intensity 8 (8-10), and duration 24 hours (12-24). Patients trialed 10 (±5.8) NB and 11.7 (±9) BTX cycles.Postoperatively, headache frequency was 5 (0-16) days/month (p<0.01), intensity 4 (0-6) (p<0.01) and duration 10 (0-24) hours (p<0.01). Median patient-reported percent resolution of ON headaches was 80% (70-85%). All patients reported improvement of comorbid headache disorders, most commonly migraine, and a reduction, discontinuation, or increased effectiveness of medications, NB and BTX.All patients who underwent treatment for refractory ON by a headache specialist and plastic surgeon benefited from nerve decompression surgery in various degrees. The collaborative selection criteria employed in this study may be replicable in clinical practice.